Effect of wholewheat flour particle shape obtained by different milling processes on physicochemical characteristics and quality of bread - Navarro, José Luis (2020)
Wholewheat flour is a very good source of nutritional compounds and functional ingredients for human diet. However, it causes negative effect on bread quality. Different milling techniques can be used to obtain wholewheat flour, minimizing the negative effect of both bran and germ on bread quality. The aim of this work is to study the effect of particle size and shape of wholegrain flour on the interaction among the different components, water distribution, dough rheology and bread volume.Experimental approach. Wholewheat flour of three varieties (Klein Rayo, Fuste and INTA 815) was obtained in cyclonic, hammer and roller mills. The characteristics of wholewheat flour were explored, and the water distribution and rheological properties of dough were determined by thermogravimetric analysis and Mixolab test, respectively. Finally, microscale bread was prepared.Results and conclusions. The amount of water-soluble pentosans, damaged starch and wet gluten was affected by the milling procedure. Regarding dough rheological properties, wholewheat flour obtained in hammer mill had the lowest water absorption capacity and the highest developing time. This result could be mainly attributed to particle shape in these samples with large amount of endosperm attached to the bran, hindering protein unfolding. Thermogravimetric analysis showed that both fine and large bran particle size seem to have the same effect on water properties in wholewheat dough during heating. Bread made with Klein Rayo variety had the highest specific volume, indicating that wheat with high protein content and breadmaking quality is needed to make wholewheat bread. The results of this work showed that particle shape, rather than particle size, affected the quality of wholewheat flour for breadmaking.Novelty and scientific contribution. Milling type and particle shape of the wholewheat flour had a greater effect than the wheat variety. Thus, the wholegrain milling process should be carefully selected taking into account the shape of the produced particle. This may open new opportunities for developing wholewheat bread with better acceptance by consumers.